2009
DOI: 10.2197/ipsjtcva.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Influences of Camera Warm-Up Effects on Image Acquisition

Abstract: This article presents an investigation of the impact of camera warm-up on the image acquisition process and therefore on the accuracy of segmented image features. Based on an experimental study we show that the camera image is shifted to an extent of some tenth of a pixel after camera start-up. The drift correlates with the temperature of the sensor board and stops when the camera reaches its thermal equilibrium. A further study of the observed image flow shows that it originates from a slight displacement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…They found that the image coordinate would drift to some tenth of a pixel during the first hour after camera start-up. To explain the reasons for the observed image coordinate drift, Handel 16 and Podbreznik and Potocnik 17,18 both established mathematical models based on pinhole model for modeling the effect of camera self-heating. Their models assume that temperature will not affect the intrinsic camera parameters and only translation of the camera needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the image coordinate would drift to some tenth of a pixel during the first hour after camera start-up. To explain the reasons for the observed image coordinate drift, Handel 16 and Podbreznik and Potocnik 17,18 both established mathematical models based on pinhole model for modeling the effect of camera self-heating. Their models assume that temperature will not affect the intrinsic camera parameters and only translation of the camera needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the effect of temperature on detection instruments are available [20,25,26]. Unfortunately, the effect of temperature on projection instruments is very difficult to describe and model.…”
Section: Discussionmentioning
confidence: 99%
“…The basics of our methods are shown in Figure 4. The most critical assumption of our method is that scanner is calibrated at a constant reference temperature after reaching thermal equilibrium (the warming-up process can take up to 1 h, depending on the camera unit and projector unit [39][40][41][42][43]45,46]). The proper calibration process allows calculation of the camera and projector location and orientation in the calibrated co-ordinate system [15,29,[55][56][57][58][59] (Figure 4, box 1 to 2a).…”
Section: Basics Of the Compensation Modelmentioning
confidence: 99%
“…The influence of temperature on images captured by digital cameras is an issue which has been described in the literature, and there exist methods for compensation of this effect [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%